The influence of adolescents’ self-perception of social relationships on personality functioning in the context of inclusive education - Hartmann, Anne; Knigge, Michel; Lenkeit, Jenny; Ehlert, Antje; Goth, Kirstin; Spörer, Nadine (Frontiers in Psychology, 2024)
Adolescence is a special phase of life in which fundamentals of psychosocial functioning are formed. The present study investigates how adolescents' self-perception of social relationships in inclusive classes affect personality functioning. Furthermore, Wwe assume examine that whether the association between self-perceived social relationships and personality functioning is stronger for students with special educational needs in the domains of learning (SEN L) and social-emotional development (SED) than for students without SEN. At two measurement points questionnaire data was collected from 927 sixth-and seventh-graders from 20 primary and 20 comprehensive inclusive classes in Germany. Results of longitudinal multilevel analyses show partially different results for sixth-and seventh-graders. Overall, students' perceived social relatedness predicted personality functioning. Students who perceived their social relationships more positively showed healthier personality functioning. Further, SEN SED represents a potential risk factor for personality functioning. But, we observed that differences in personality functioning between seventh-graders with SEN L or SED and those without SEN decreased over time. Furthermore, SEN does not appear to reinforce the association between low self-perception of social relationships and risky personality functioning. The findings are discussed in the context of inclusive education and implications for future research as well as practice are given. Overall, our findings contribute to a better understanding of students' psychosocial development in inclusive learning environments.Note: Longitudinal multilevel hierarchical regression analysis; Time = change from t1 to t2; *p < .05.